2019
DOI: 10.3390/su11236643
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to the Relationship between Driving Mileage and Crash Frequency of Older Drivers

Abstract: As a characteristic of senior drivers aged 65 +, the low-mileage bias has been reported in previous studies. While it is thought to be a well-known phenomenon caused by aging, the characteristics of urban environments create more opportunities for crashes. This calls for investigating the low-mileage bias and scrutinizing whether it has the same impact on other age groups, such as young and middle-aged drivers. We use a crash database from the Ohio Department of Public Safety from 2006 to 2011 and adopt a macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Since drivers in China break traffic law more often than those in developed countries [2], we are interested in factors related to traffic enforcement, such as traffic police numbers and the number of road cameras. The relation between traffic safety and a lot more factors, such as roadway infrastructure [48,49], advanced control schemes [50], vehicle mileage traveled [51], and vehicle market predictions [52] are also worthy of being explored. Without a city-level dataset on the aforementioned variables, we may adopt statistical data fusion approaches, such as density ratio fusion [53], to obtain a comprehensive traffic safety dataset with the aforementioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…Since drivers in China break traffic law more often than those in developed countries [2], we are interested in factors related to traffic enforcement, such as traffic police numbers and the number of road cameras. The relation between traffic safety and a lot more factors, such as roadway infrastructure [48,49], advanced control schemes [50], vehicle mileage traveled [51], and vehicle market predictions [52] are also worthy of being explored. Without a city-level dataset on the aforementioned variables, we may adopt statistical data fusion approaches, such as density ratio fusion [53], to obtain a comprehensive traffic safety dataset with the aforementioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been several studies in the recent past on macro-level safety models, where spatially aggregated accidents are modeled against area-wide variables. These studies have employed various aggregation levels, such as census tracts, traffic analysis zones, counties, cities, states, and countries [39,40]. Attributes of these spatial aggregations, such as population, density, income, land use characteristics, environmental variables, traffic characteristics, trip generation rates, road density, etc., are typically used to model crashes.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, ITV records can be used to search for mobility patterns, in relation to kilometers traveled and vehicle age [34], or the differences between travel patterns, depending on rural and urban areas and the dependence on vehicle age [35]. It is even possible to establish relationships between the kilometers traveled and the frequency of accidents involving drivers of different ages [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result of the literature review, it was identified that the survey method has been used to obtain data [36,[38][39][40][41]46,[51][52][53][54][55][56] and is potentially subject to bias [35,49]. Its massive application to road safety studies in practice becomes impossible and economically unfeasible, limited by the volume and geographical origin of the same [34].…”
Section: Literature Reviewmentioning
confidence: 99%